2014
DOI: 10.1128/jvi.03059-13
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Foot-and-Mouth Disease Virus Nonstructural Protein 3A with Host Protein DCTN3 Is Important for Viral Virulence in Cattle

Abstract: Nonstructural protein 3A of foot-and-mouth disease virus (FMDV) is a partially conserved protein of 153 amino acids in most FMDVs examined to date. The role of 3A in virus growth and virulence within the natural host is not well understood. Using a yeast two-hybrid approach, we identified cellular protein DCTN3 as a specific host binding partner for 3A. DCTN3 is a subunit of the dynactin complex, a cofactor for dynein, a motor protein. The dynactin-dynein duplex has been implicated in several subcellular funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 28 publications
2
39
0
Order By: Relevance
“…This is in contrast to those of previous studies showing that chimeric viruses containing 3A of O/TAW/97 grew poorly and cannot form plaques in bovine cell (Beard and Mason, 2000), and that Asia 1 recombinant virus containing deletion at positions 93-102 or 91-104 in 3A failed to replicate and produce plaque in primary bovine kidney cells (Li et al, 2010. However, this conclusion is consistent with a recent report showing that aa substitution at positions 89-92 in 3A affect FMDV replication and plaque formation in primary bovine cells (Gladue et al, 2014). Furthermore, the result of quantification analysis of viral RNA also proves that the deletion at positions 93-102 in 3A, indeed, affect virus replication efficiency in primary cells of bovine origin, but cannot alone GZSB-WT 10 −5 5 5 0 100 10 −6.833 10 −6 5 5 0 100 10 −7 5 2 3 40 account for the inability to replicate in bovine cells.…”
Section: Discussionsupporting
confidence: 84%
“…This is in contrast to those of previous studies showing that chimeric viruses containing 3A of O/TAW/97 grew poorly and cannot form plaques in bovine cell (Beard and Mason, 2000), and that Asia 1 recombinant virus containing deletion at positions 93-102 or 91-104 in 3A failed to replicate and produce plaque in primary bovine kidney cells (Li et al, 2010. However, this conclusion is consistent with a recent report showing that aa substitution at positions 89-92 in 3A affect FMDV replication and plaque formation in primary bovine cells (Gladue et al, 2014). Furthermore, the result of quantification analysis of viral RNA also proves that the deletion at positions 93-102 in 3A, indeed, affect virus replication efficiency in primary cells of bovine origin, but cannot alone GZSB-WT 10 −5 5 5 0 100 10 −6.833 10 −6 5 5 0 100 10 −7 5 2 3 40 account for the inability to replicate in bovine cells.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, Pacheco et al reported that an O1Campos variant (O1CaD3A) harboring 20 aa deletion in 3A between residues 87-106 also displayed lower replication rate (approximately 1000-fold) in FBK cells than its parental virus O1Ca (Pacheco et al, 2013). The replication rate of O1CaD3A decreased more obviously than those of the epitopetagged viruses in FBK cells, and one possible reason is that the O1CaD3A lacked the DCTN3 binding site (residues 89-92 in 3A) since the binding between FMDV 3A and host DCTN3 may contribute to the host range specificity of FMDV (Gladue et al, 2014). On the other hand, we also analyzed the growth properties of 3A-tagged viruse (FMDV-FLAG) and its parental virus (r-HN) (Li et al, 2012) in FBK cells, and the results showed that FMDV-FLAG and r-HN replicated poorly in FBK cells with no visible plaque (data not shown).…”
Section: Discussionmentioning
confidence: 89%
“…This interaction with DCTN3 is required for virulence in cattle or cultured primary kidney cells but not in transformed kidney cell lines (30). Intriguingly, during serial passage, NSP3A mutants that reacquired virulence had mutated to reacquire DCTN3 binding (30). This underscores the importance of DCTN3 to FMDV infection in vivo and in normal cells and highlights potential dangers of studying transformed cell lines.…”
Section: Virus Entry and Internalizationmentioning
confidence: 84%
“…Foot-and-mouth disease virus (FMDV) nonstructural protein 3A (NSP3A) binds and colocalizes with DCTN3 early in infection. This interaction with DCTN3 is required for virulence in cattle or cultured primary kidney cells but not in transformed kidney cell lines (30). Intriguingly, during serial passage, NSP3A mutants that reacquired virulence had mutated to reacquire DCTN3 binding (30).…”
Section: Virus Entry and Internalizationmentioning
confidence: 99%